The United States of America’s withdrawal from Afghanistan in 2021: a critical analysis - Matola, T. (BUSE, 2023)
The study sought to analyze the United States of America’s withdrawal from Afghanistan in 2021. To achieve this goal, this study had three subsidiary objectives. Qualitative research methodology was used in carrying this study. First, the researcher analyzed the United States of America’s foreign policy towards a few selected countries in the Middle- East (Iran, Iraq, and Yemen). Second, the researcher assessed the major reasons leading to the United States of America’s military intervention in Afghanistan. Third, the researcher established factors influenced the United States of America’s withdrawal from Afghanistan as well as the implications of such a withdrawal. In so doing, this chapter provides a summary of the factors that influenced the United States of America’s withdrawal from Afghanistan as well as the implications of such a withdrawal. It analyses the United States of America’s foreign policy towards a few selected countries in the Middle- East (Iran, Iraq, and Yemen) visa vie Afghanistan. And the major reasons leading to the United States of America’s military intervention in Afghanistan are also discussed. Finally, the study recommends that further research should be carried out on the United States of America’s Withdrawal from Afghanistan in 2021.
Keywords: Foreign Policy; Middle-East; United States of America